2020
DOI: 10.2147/ccid.s230617
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlation Between Lipid Profile and Acne Vulgaris</p>

Abstract: Background and Aim: Acne is a common skin disease resulting from a complex interaction of various pathogenetic factors. The aim of this study was to find out lipid profile abnormalities in acne vulgaris patients. Material and Methods: This descriptive analytic cross-sectional study was conducted on 45 acne patients and 45 age-and sex-matched healthy controls to assess plasma total cholesterol (TC), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
7
14
0
Order By: Relevance
“…This was in concur with Sobhan et al, [20] who found that for cholesterol, a huge distinction was seen between male patients and solid partners (173.9±0.13 and 150.3±0.33 for patients and controls, separately, p=0.04).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was in concur with Sobhan et al, [20] who found that for cholesterol, a huge distinction was seen between male patients and solid partners (173.9±0.13 and 150.3±0.33 for patients and controls, separately, p=0.04).…”
Section: Discussionsupporting
confidence: 92%
“…In negate with Al Kubaisy et al, [19] who made a cross-sectional investigation led in the Syrian International University for Science and Technology, an example of 500 understudies was picked and discovered that guys have higher predominance of skin break out contrasted with females (42.9% versus 23.6%).Sobhan et al, [20] uncovered that the male to female proportion was about 1:2, however this was not factually huge (P=0.5). Li et al, [21] confirmed in their a meta-examination which was directed in terrain China found a higher pervasiveness pace of skin inflammation in guys than females, because of contrasts in way of life, skincare schedules, and androgen levels.Well, [22] uncovered that Over 90% of guys and 80% of females have encountered skin inflammation by the time of 21.Tan and Bhate, [23] study results uncovered that male patients were all the more oftentimes influenced, especially with more serious types of acne.This doesn't imply that skin inflammation is more normal in female yet it implies that young ladies are more mindful about their facial appearance than young men, and they look for treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Like our outcomes, Sobhan et al, [9] contemplated lipid profile anomalies in 45 skin inflammation vulgaris patients and 45 solid controls. They referenced that fundamentally more elevated cholesterol level in skin break out patients.…”
Section: Discussionsupporting
confidence: 55%
“…Hence, the relationship of diet and acne development is still disputed ( Bowe et al, 2010 ).The importance of sebaceous glands in acne pathogenesis and evidence that its activity is modulated by dietary lipids provoked many researchers to study association of serum lipids in acne patients ( Sobhan et al, 2020 ). Recently, elevated expression of apolipoprotein a (apo-a), a core protein component of high density lipoprotein cholesterol (HDL-C) has been identified in a proteome analysis of the follicle infundibulum in acne patients ( Bek-Thomsen et al, 2014 ) Increased levels of total cholesterol (TC), but decreased levels of HDL-C and apo-a were consistently observed in acne patients from different populations ( Jiang et al, 2015 , Sobhan et al, 2020 ). In addition, El-Akawi and colleagues reported that serum HDL-C levels decrease with increase in acne severity ( El-Akawi et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%